2010
DOI: 10.1186/1471-2164-11-340
|View full text |Cite
|
Sign up to set email alerts
|

Classifying genes to the correct Gene Ontology Slim term in Saccharomyces cerevisiae using neighbouring genes with classification learning

Abstract: BackgroundThere is increasing evidence that gene location and surrounding genes influence the functionality of genes in the eukaryotic genome. Knowing the Gene Ontology Slim terms associated with a gene gives us insight into a gene's functionality by informing us how its gene product behaves in a cellular context using three different ontologies: molecular function, biological process, and cellular component. In this study, we analyzed if we could classify a gene in Saccharomyces cerevisiae to its correct Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Moreover, using Gene Ontology Slim17, the largest values for genes were also detected in R. solani AG1 IA (Supplementary Fig. S4, Supplementary Note 4).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, using Gene Ontology Slim17, the largest values for genes were also detected in R. solani AG1 IA (Supplementary Fig. S4, Supplementary Note 4).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that, although the co‐regulation of genes mediated by TFs would potentially be sufficient, an even more efficient co‐regulation of such functionally related genes would be more efficient when being co‐localized in the same region of a chromosome, reducing the burden of unpacking the DNA from its histone‐wrapped state prior to transcription. A recent study has further underlined this hypothesis, as over 80% of S. cerevisiae genes have been successfully assigned to their correct Gene Ontology Slim term by using information about the localization of each gene's two‐nearest neighbors, highlighting the extensive use of co‐localization of functionally related gene clusters in this host system (Amthauer and Tsatsoulis, ). Considering the similar fold change ranges of the significantly up‐regulated genes in C.U17 EWK which were pinpointed within the designated chromosome IV locus, our data suggest the existence of a physical cluster of genes which are related to protein maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In this project, she has to identify some of unknown genes functions. She focused on an experiment that states the gene function can be identified by knowing the gene location and the Gene Ontology Slim information from neighbouring genes [Amthauer and Tsatsoulis, 2010]. Since getting information from images is less time-consuming than looking through numbers and texts, she needs software that helps her to visualize the genes location in the chromosome and shows the GO Slims distribution in the chromosome.…”
Section: Research Limitations and Future Workmentioning
confidence: 99%